Penerapan Pendekatan Konstruktivistik Dalam Meningkatkan Hasil Belajar IPA Terpadu SMP Negeri 1 Gunungsitoli Idanoi Tahun Pelajaran 2023/2024 - Tentiani Zebua (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2024)
The low learning outcomes and limited active participation of students in Integrated Science learning remained major problems at SMP Negeri 1 Gunungsitoli Idanoi. Teacher-centered learning processes caused students to experience difficulties in constructing conceptual understanding independently, resulting in learning outcomes that had not yet achieved the minimum mastery criteria. This study aimed to improve the quality of the learning process and students’ learning outcomes through the implementation of a constructivist approach. The study was conducted using Classroom Action Research (CAR), consisting of two cycles involving planning, action, observation, and reflection stages. The research subjects were 30 students of class VIII-C at SMP Negeri 1 Gunungsitoli Idanoi in the 2023/2024 academic year. Data were collected through observation, questionnaires, interviews, documentation, and learning achievement tests, then analyzed using descriptive quantitative and qualitative techniques. The findings revealed that the implementation of the constructivist approach increased students’ active participation from 62.72% in Cycle I to 89.79% in Cycle II. Students’ average learning outcomes also improved from 65.31 to 82.12, with learning mastery reaching 93.33%. These findings indicated that the constructivist approach was effective in creating a more active, meaningful, and student-centered Integrated Science learning environment.